Crystal structure of a cross-reaction complex between an anti-HIV-1 protease antibody and an HIV-2 protease peptide - Rezacova, Pavlina; Brynda, Jiri; Lescar, Julien; Fabry, Milan; Horejsi, Magda; Sieglova, Irena; Sedlacek, Juraj; Bentley, Graham A (Journal of structural biology, 2005)
The monoclonal antibody 1696, elicited by HIV-1 protease, inhibits the activity of both HIV-1 and HIV-2 proteases with inhibition constants in the low nanomolar range. The antibody cross-reacts with peptides derived from the N-terminal region of both proteases. The crystal structure of the recombinant single-chain Fv fragment of 1696 complexed with an N-terminal peptide from the HIV-2 protease has been determined at 1.88A resolution. Interactions of the peptide with scFv1696 are compared with the previously reported structure of scFv1696 in complex with the corresponding peptide from HIV-1 protease. The origin of cross-reactivity of mAb1696 with HIV proteases is discussed.
Keywords: Cross Reactions; monoklonální protilátky; krystalografie rentgenová; zkřížené reakce; aspartátové endopeptidasy; Aspartic Acid Endopeptidases; molekulární sekvence - údaje; Amino Acid Sequence; sekvenční seřazení; molekulární modely; Crystallography, X-Ray; Models, Molecular; HIV protilátky; HIV Antibodies; lidé; HIV Protease; konformace proteinů; Humans; HIV-proteasa; Peptides; sekvence aminokyselin; peptidy; Molecular Sequence Data; Protein Conformation; Antibodies, Monoclonal; Sequence Alignment